6
$\begingroup$

I want to price Binary Option in Black-Scholes model.

The payoff is of the form $f(S_{T})=I_{\{S_{T}-K>0\}}$.

If we assume that $t=0$ this is easy, because then we have

$C_{0}=\mathbb{E}^{*}\left[e^{-rT}I_{\{S_{T}-K>0\}}|F_{0}\right]=e^{-rT}\mathbb{E}^{*}\left[I_{\{S_{T}-K>0\}}\right]=e^{-rT}Q(S_{T}>K)=\ldots$

But how to derive a price at any time $t\in[0,T]$?

For any $t\in[0,T]$ we have something like this:

$C_{t}=\mathbb{E}^{*}\left[e^{-r(T-t)}I_{\{S_{T}-K>0\}}|F_{t}\right]=e^{-r(T-t)}\mathbb{E}^{*}\left[I_{\{S_{T}-K>0\}}|F_{t}\right]=?$

How to compute $\mathbb{E}^{*}\left[I_{\{S_{T}-K>0\}}|F_{t}\right]$?

My attempt:

$S_{T}=S_{t}e^{(r-\frac{1}{2}\sigma^{2})(T-t)+\sigma(W^{*}_{T}-W^{*}_{t})}$

I know that $W^{*}_{T}-W^{*}_{t}$ is independent with respect to $F_{t}$ (generated by Brownian Motion).

Does $I_{\{S_{T}-K>0\}}$ is independent with respect to $F_{t}$? Why (if yes)?

If yes $\mathbb{E}^{*}\left[I_{\{S_{T}-K>0\}}|F_{t}\right]=\mathbb{E}^{*}\left[I_{\{S_{T}-K>0\}}\right]=Q(S_{T}-K>0)=\ldots$

$\endgroup$
6
$\begingroup$

$I_{\{S_{T}-K>0\}}$ is NOT independent of $\mathcal{F}_{t}$, since \begin{align*} S_T=S_t \, e^{(r-\frac{1}{2}\sigma^2)(T-t) + \sigma (W_T^*-W_t^*)}, \end{align*} where $S_t \in \mathcal{F}_t$, though $e^{(r-\frac{1}{2}\sigma^2)(T-t) + \sigma (W_T^*-W_t^*)}$ is independent of $\mathcal{F}_t$. However, since $W_T^*-W_t^*$ is independent of $\mathcal{F}_t$, you are able to compute \begin{align*} \mathbb{E}^{*}\left(I_{\{S_{T}-K>0\}}|F_{t}\right) &= Q(S_{T}-K>0 \mid \mathcal{F}_t)\\ &=Q\left(\sigma (W_T^*-W_t^*) \ge \ln\frac{K}{S_t} -(r-\frac{1}{2}\sigma^2)(T-t) \mid \mathcal{F}_t\right)\\ &=Q\left(\frac{W_T^*-W_t^*}{\sqrt{T-t}} \ge \frac{\ln\frac{K}{S_t} -(r-\frac{1}{2}\sigma^2)(T-t)}{\sigma \sqrt{T-t}} \mid \mathcal{F}_t\right)\\ &=1-N\left( \frac{\ln\frac{K}{S_t} -(r-\frac{1}{2}\sigma^2)(T-t)}{\sigma \sqrt{T-t}}\right)\\ &=N(d_2), \end{align*} since $\frac{W_T^*-W_t^*}{\sqrt{T-t}}\sim N(0, 1)$ is independent of $\mathcal{F}_t$, while $\frac{\ln\frac{K}{S_t} -(r-\frac{1}{2}\sigma^2)(T-t)}{\sigma \sqrt{T-t}}$ is $\mathcal{F}_t$ measurable. Here, $$d_2 = \frac{\ln\frac{S_t}{K} + (r-\frac{1}{2}\sigma^2) (T-t)}{\sigma \sqrt{T-t}}$$

$\endgroup$
  • $\begingroup$ Could you edit your post and show me how to compute $Q(S_{T}-K>0|F_{t})=N(d_{2})$. The question is how to deal with conditioning with respect to $F_{t}$. $\endgroup$ – Leon Mar 4 '16 at 7:08
  • $\begingroup$ I think I found a clear justification how to pass from $Q(S_{T}-K>0|F_{t})$ to $N(d_{2})$. Could you check it? $\endgroup$ – Leon Mar 12 '16 at 18:31
4
$\begingroup$

You can also infer the value of your binary option from the value of a European call option with the same strike and time-to-maturity by going long on a call with strike $K$ and time-to-maturity $\tau$, and short on a call with strike $K+\Delta K$ and the same time-to-maturity. If you hold $\frac{1}{\Delta K}$ of that portfolio, then as $\Delta K$ goes to zero, your total payoff becomes closer to the payoff of the binary option.

If you denote by $V_t$ the value of your binary option, and $C_t \left(\tau ,K \right)$ the value of a European call option with strike $K$ and expiring at $t+\tau$, then it is easy to see the following :

$$V_t = \lim_{\Delta K \to 0} \frac{1}{\Delta K} \left( C_t\left(\tau,K\right)-C_t\left(\tau,K+\Delta K\right) \right)$$

Basically the value of the binary option is the opposite of the partial derivative of the price of a European call option of the same strike and time-to-maturity with respect to the strike, ie :

$$V_t = - \frac{\partial C_t}{\partial K} \left( \tau, K \right)$$ $$=-\frac{\partial}{\partial K} \left( e^{-q\tau} S_t \mathcal{N}\left( d_1 \right) - e^{-r \tau} K \mathcal{N}\left( d_2 \right) \right)$$ $$=e^{-r\tau} \mathcal{N} \left( d_2 \right)$$

$\endgroup$
3
$\begingroup$

I think that I found correct answer to my question.

We have the following theorem:


Theorem. If $X$ is independent of $\mathcal{G}$, $Y$ is $\mathcal{G}$ - measurable and $\phi(x,y)$ is bounded function then:

$$E\left[\phi(X,Y)|\mathcal{G}\right]=E\left[\phi(X,y)\right]$$


In my problem I want to calculate the following formula:

$C_{t}=\mathbb{E}^{*}\left[e^{-r(T-t)}I_{\{S_{T}-K>0\}}|F_{t}\right]=e^{-r(T-t)}\mathbb{E}^{*}\left[I_{\{S_{T}-K>0\}}|F_{t}\right]=\ldots $

so if i rewrite $S_{T}$ as $S_{T}=S_{t}e^{(r-\frac{1}{2}\sigma^{2})(T-t)+\sigma(W^{*}_{T}-W^{*}_{t})}$ i will get something like this:

$$S_{T}=Y\cdot e^{(r-\frac{1}{2}\sigma^{2})(T-t)+\sigma\cdot X}$$

where $Y$ is $F_{t}$ - measurable and $X$ is independent of $F_{t}$.

Moreover, we can define $\phi(x,y)=I_{\{y\cdot e^{C+D\cdot x}-K>0\}}$ which is bounded.

It means that using the above theorem we get:

$$\ldots=e^{-r(T-t)}\mathbb{E}^{*}\left[I_{\left\{S_{t}e^{(r-\frac{1}{2}\sigma^{2})(T-t)+\sigma(W^{*}_{T}-W^{*}_{t})}-K>0\right\}}|F_{t}\right]$$ $$=e^{-r(T-t)}\mathbb{E}^{*}\left[I_{\left\{S_{t}e^{(r-\frac{1}{2}\sigma^{2})(T-t)+\sigma(W^{*}_{T}-W^{*}_{t})}-K>0\right\}}\right]$$ $$=e^{-r(T-t)}Q\left(S_{t}e^{(r-\frac{1}{2}\sigma^{2})(T-t)+\sigma(W^{*}_{T}-W^{*}_{t})}-K>0\right)=\ldots$$

and this is what we want.

Comments.

You are basically correct. For any two independent random variables $X$ and $Y$, the theorem says that \begin{align*} E\big(\phi(X, Y) \mid \mathcal{G} \big) = E\big(\phi(X, y) \,\big)\, |_{y=Y}. \end{align*} Here, for the conditional expectation, \begin{align*} \mathbb{E}^*\bigg(I_{\big\{S_{t}e^{(r-\frac{1}{2}\sigma^{2})(T-t)+\sigma(W^*_{T}-W^*_{t})}-K>0\big\}} \mid \mathcal{F}_{t}\bigg) &= \mathbb{E}^*\bigg( I_{\big\{s\,e^{(r-\frac{1}{2}\sigma^{2})(T-t)+\sigma(W^*_{T}-W^*_{t})}-K>0\big\}} \bigg)\,\Big|_{s=S_t}\\ &= N(d_2). \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.